399 Cosibelimab, an anti-PD-L1 antibody: preliminary safety and efficacy results from a global, multicohort phase 1 clinical trial. (9th November 2020) - Harris, Dean; Brungs, Daniel; Ladwah, Rahul; Mant, Andrew; McGrath, Margaret; Tazbirkova, Andrea; Akopov, Andrey; Fadeeva, Natalia; Kasparov, Boris; Kovalenko, Nadezhda; Kozlov, Vadim; Moiseenko, Fedor; et al.
Abstract : Background: Cosibelimab is a high affinity, fully-human IgG1 monoclonal antibody that directly binds to programmed death ligand-1 (PD-L1) and blocks its interaction with the programmed death receptor-1 (PD-1) and B7.1 receptors to restore an anti-tumor immune response. Cosibelimab has the additional benefit of a functional Fc domain capable of inducing antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity against tumor cells. Study CK-301–101 is a global, multicenter, multicohort trial that is enrolling patients (pts) with select advanced cancers, including pivotal cohorts of pts with metastatic and locally advanced cutaneous squamous cell carcinoma (cSCC) and a cohort of pts with previously untreated advanced non-small cell lung cancer (NSCLC). Methods: Eligible pts were aged ≥18 years with an Eastern Cooperative Oncology Group performance status of 0–1. The cSCC cohorts enrolled pts with histologically confirmed metastatic or locally advanced cSCC not amenable to local therapy. The NSCLC cohort enrolled previously untreated NSCLC pts with advanced disease and a PD-L1 tumor proportion score of at least 50%. Pts received a fixed dose of 800 mg cosibelimab administered intravenously every two weeks. Anti-tumor activity was assessed by Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 and were conducted every 8 weeks for the initial 32 weeks on study, and every 12 weeks thereafter. Results: As of August 2020, 114 pts (73M/41F, median age 66 years) with diverse tumor types have been enrolled and treated with cosibelimab. Among these pts, 103 (90%) experienced ≥1 treatment-emergent adverse event (AE), 42 (37%) experienced a grade ≥3 AE, and 6 (5%) experienced a grade ≥3 drug-related AE. The most common AEs were fatigue (25%), anemia (21%), rash (18%) and nausea (16%) and the most common drug-related AEs were fatigue (15%) and rash (14%). In 42 cSCC pts evaluable for response, ORR based on investigator assessment of tumor response was 55% (95% confidence interval [CI]: 39, 70), including 5 (12%) complete responses, with 20/23 (87%) responses ongoing and 10 responses ≥6 months in duration as of data cutoff. In 25 NSCLC pts evaluable for response, ORR based on investigator assessment was 44% (95% CI: 24, 65), with 5/11 (45%) responses ongoing and 10 responses ≥6 months in duration. Conclusions: Cosibelimab has a predictable and manageable safety profile and demonstrated robust clinical activity in cSCC and NSCLC pts, including durable complete and partial responses. Updated results will be presented. Trial Registration: NCT03212404 Ethics Approval: The study was approved by an appropriate ethics committee for each participating institution. Informed consent was obtained for all subjects. Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal.